Dietary Qi-Weng-Huangbo powder enhances growth performance, diarrhoea and immune function of weaned piglets by modulating gut health and microbial profiles - Xiao, Chuanpi; Li, Kai; Teng, Chunran; Wei, Zeou; Li, Jiaheng; Zhang, Shunfeng; Liu, Lei; Lv, Huiyuan; Zhong, Ruqing (Frontiers in Immunology, 2023)
The evolution of nutritional strategies to improve the gut health and microbiota profiles of early-weaned piglets is essential to reduce diarrhoea caused by weaning stress. Therefore, the aim of this study was to determine the effects of dietary supplementation of Qi-Weng-Huangbo powder, a traditional herbal medicine consisting of a mixture of Pulsatilla chinensis, Chinese Schneid and Astragalus extracts (PCE), on the growth performance, diarrhoea rate, immune function and intestinal health of weaned piglets. 162 piglets were randomly assigned to the CON group (no PCE added), the PCEL group (300 mg/kg PCE) and the PCEH group (500 mg/kg PCE) at the end of the third week post farrowing. There were 9 replicates of each group with 6 pigs per replicate. The experiment lasted for 28 days and sampling was performed on the final day. The results showed that the PCE diet increased the average daily gain (ADG) and final body weight (BW) compared to the CON group. Both supplemented doses of PCE reduced the faecal scores of piglets, and the diarrhoea rate in the PCEL group was significantly lower than that in the CON group. The application of PCE diets promoted the development of the spleen in piglets and up-regulated serum immunoglobulin concentrations to enhance immune function, which was also reflected in the down-regulated gene expression of the colonic TLR/MyD88/NF-κB pathway. Supplementation with PCE improved intestinal morphology, and all doses of PCE significantly increased villus height (VH) in the ileum, whereas colonic crypt depth (CD) was significantly lower in the PCEH group than in the CON group. The PCEH diet significantly increased the levels of valeric and isovaleric acid in the colon content. Dietary PCEH also improved the colonic microbial community profile, reflected by a significant increase in Shannon's index compared with CON group. The abundance of Veillonellaceae and Rhodospirillales was significantly increased in the PCEH group at the family level. In conclusion, dietary PCE reduced diarrhoea rates, improved growth performance and enhanced immune function in weaned piglets. These improvements were potentially supported by altered ileum and colonic morphology, elevated colonic VFA levels, and modulation of colonic microbial profiles.